2012
DOI: 10.5657/fas.2012.0305
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Responses of Nile Tilapia Oreochromis niloticus under Different Feed-Deprivation Regimes

Abstract: We investigated compensatory growth of Nile Tilapia Oreochromis niloticus in structural size and live weight in response to different deprivation periods and refeeding. Four treatments were assigned randomly to fish in 12 glass tanks, with each treatment performed in triplicate. The control group was fed to satiation three times a day throughout the experiment. The other three treatment groups were starved for 1 week (S1), 2 weeks (S2), or 4 weeks (S4) and then fed until the end of the experiment. After the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 35 publications
1
25
1
1
Order By: Relevance
“…Correspondingly, hybrid tilapia juveniles (O. niloticus x O. aureus) deprived of feed 3 days per week presented poor growth compared to those deprived for 1 and 2 days, respectively (Abdel-Hakim et al, 2009). Poor compensatory growth in fish exposed to longer deprivation periods were also reported in Nile tilapia (Gao & Lee, 2012;Passinato et al, 2015), O. mossambicus (Christensesn & Mclean, 1998), and in other species such as Centropomus parallelus (Ribeiro & Tsuzuki, 2010) and Sparus aurata (Peres, Santos, & Oliva-Teles, 2011).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Correspondingly, hybrid tilapia juveniles (O. niloticus x O. aureus) deprived of feed 3 days per week presented poor growth compared to those deprived for 1 and 2 days, respectively (Abdel-Hakim et al, 2009). Poor compensatory growth in fish exposed to longer deprivation periods were also reported in Nile tilapia (Gao & Lee, 2012;Passinato et al, 2015), O. mossambicus (Christensesn & Mclean, 1998), and in other species such as Centropomus parallelus (Ribeiro & Tsuzuki, 2010) and Sparus aurata (Peres, Santos, & Oliva-Teles, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…They further indicated that moderate feed deprivation regime (1, and 2 days per week) showed a significant reduction in feeding costs. Moreover, full compensatory growth was reported in Nile tilapia (Passinato et al, 2015;Cuvin-Aralar et al, 2012;Gao & Lee, 2012); Lates calcarifer (Tian & Qin, 2004) subjected to different feed restriction /refeeding regimes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The compensatory capacity of Nile tilapia is controversial; some studies indicate complete compensation, whereby the feed restricted fish eventually achieve the same weight as fish that are continuously fed (Gao & Lee, ; Wang, Cui, Yang, & Cai, ). In contrast, other evaluations have indicated that the Nile tilapia only possess partial compensatory capacity, meaning that the fish increase their weight during feeding following a period of feed restriction, but do not reach the same weight as those fish that have continuous access to feed (Cho, ; Wang, Li, Qin, & Han, ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, other evaluations have indicated that the Nile tilapia only possess partial compensatory capacity, meaning that the fish increase their weight during feeding following a period of feed restriction, but do not reach the same weight as those fish that have continuous access to feed (Cho, ; Wang, Li, Qin, & Han, ). It is important to indicate that the physiological processes that regulate the compensatory response are poorly understood (Won & Borski, ) and can be influenced by distinct factors such as the period of feed restriction and feeding, age, sex, environmental factors, hyperphagia and depletion of energy reserves, among others (Ali et al, ; Gao & Lee, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The relative wellbeing in fish can be assessed through length-weight and length-length relationships (King, 1996). These relationships have been widely used on different fish species in the laboratory researches to study the effects of certain ingredients or diet-borne toxins (Ogunji et al, 2008;Ghazalah et al, 2010;Gao and Lee, 2012) and in the field investigations to understand the effect of water quality on the growth performance of fish (Taiwo and Aransiola, 2001;Fafioye and Oluajo, 2005;Laleye, 2006) Gel electrophoresis is a broad subject encompassing many different techniques. Sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) is the most commonly practiced technique used to separate proteins according to their molecular weights (Jesslin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%